DOI: 10.33915/etd.3112
|View full text |Cite
|
Sign up to set email alerts
|

The effects of riparian tree harvest intensity and woody debris addition on biotic and abiotic stream characteristics

Abstract: The effect of riparian tree harvest intensity on biotic and abiotic stream characteristics Jered Michael Studinski Forested headwater streams rely on riparian zones for many critical products and services. Riparian areas shade streams, stabilize stream banks, filter sediment, and provide allochthonous materials like leaves, large woody debris (LWD), and terrestrial invertebrates (TI's). Logging can affect the products and services of riparian zones. Best management practices (BMP's) have been developed to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…Low terrestrial biomass may characterise streams in the Appalachian Mountains because other studies in this region have also found low terrestrial biomass (e.g. 17.3 mg m À2 day À1 seeRomaniszyn, Hutchens & Wallace, 2007;Studinski, 2010); however, values from our study in the Ridge and Valley region of Virginia are a magnitude lower than similar-© 2013 John Wiley & Sons Ltd, Freshwater Biology, 58, 2423-2438…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Low terrestrial biomass may characterise streams in the Appalachian Mountains because other studies in this region have also found low terrestrial biomass (e.g. 17.3 mg m À2 day À1 seeRomaniszyn, Hutchens & Wallace, 2007;Studinski, 2010); however, values from our study in the Ridge and Valley region of Virginia are a magnitude lower than similar-© 2013 John Wiley & Sons Ltd, Freshwater Biology, 58, 2423-2438…”
contrasting
confidence: 64%
“…Low terrestrial biomass may characterise streams in the Appalachian Mountains because other studies in this region have also found low terrestrial biomass (e.g. 17.3 mg m −2 day −1 see Romaniszyn, Hutchens & Wallace, ; Studinski, ); however, values from our study in the Ridge and Valley region of Virginia are a magnitude lower than similar‐sized streams located in the Piedmont region of Virginia possibly due to the large differences in geology and vegetation between these two regions (Cloe & Garman, ). Additionally, intermittency can play a role in this regional variation because intermittent streams may have different vegetation or provide unique habitat or microclimate conditions that lead to low terrestrial biomass (Steward et al ., ; Katz, Denslow & Stromberg, ).…”
Section: Discussionmentioning
confidence: 60%
“…This is especially true for Rainbow Trout Oncorhynchus mykiss and other salmonids that tolerate a relatively narrow range of temperatures. Unfortunately, the amount of suitable habitat available for coldwater species is decreasing due to greenhouse gasses increasing air temperatures (Eaton and Scheller 1996;Morrill et al 2005), urbanization (Nelson and Palmer 2007), deforestation (Brown and Krygier 1970;Baillie et al 2005;Studinski 2010), and other anthropogenic activities. With a doubling of atmospheric carbon dioxide (CO 2 ), Rainbow Trout could lose up to 49.1% of their current habitat due to a rise in stream temperatures across the USA (Eaton and Scheller 1996).…”
mentioning
confidence: 99%
“…Invertebrates were placed into bottles and preserved in 80% ethanol. For more detailed analysis of this study please seeStudinski 2010.…”
mentioning
confidence: 99%